ANALISIS PERBANDINGAN DIAGNOSTIC REFERENCE LEVEL (DRL) MODALITAS CT SCAN SEBAGAI UPAYA OPTIMASI PROTEKSI DAN KESELAMATAN RADIASI DI BERBAGAI NEGARA - Duandini, Ega; Etika, Eva Anggun; Nurulita, Syaphira Faza; Hidayanto, Eko (BERKALA FISIKA, 2021)
Computed  Tomography  (CT)  Scan  had  grown  since  its  first  discover  at  1972.  Now,  CT  Scan  is the  most  capable  radiodiagnostic  modality  for  detecting  human  anatomy  in  a  short  time. However, CT Scan has the highest dose among another radiodiagnostic modalities. If radiation dose  exposure  exceeds  the  limit,  it  will  cause  any  serious  disease,  such  as  cancer.  Based  on Mathews  et  al  research  in  Australia,  in  2016,  there  are  3150  from  680211  cancer  patient  ever exposured by CT Scan one year before. From the research,  it is known that there is effect after exposured  by  CT  Scan.  Therefore,  supervision  is  needed  in  an  effort  to  ensure  protective efficiency  and  safety  of  radiation  against  radiation  workers,  patients  and  communities,  among them with the diagnostic reference level (DRL). The DRL is the value of a dose or rate of dosage or  activity  established  by  a  data  dose  or  rate  of  dosage  or  activity  that  X-ray  medical examinations  result  from  each  type  of  examination.  The  value  of  the  DRL  is  recommended  on quartile  3  (75  percentiles)  of  a  fragmented  dose  data  obtained  from  the  median  value.  This research  focused  on  the  CT  scan  modality  for  inspection.  And  obtained  CTDIvol  and  DLP grades.  In  this  research,  obtainer  DRL  value  for  CT  Chest  10.99  mGy  CTDIvol  and  411.71 mGy.cm DLP, and for CT Abdomen 17.84 mGy CTDIvol and 1298.58 mGy.cm DLP.